2014
DOI: 10.1155/2014/579242
|View full text |Cite
|
Sign up to set email alerts
|

Small Fiber Neuropathy Associated with Hyperlipidemia: Utility of Cutaneous Silent Periods and Autonomic Tests

Abstract: Background. Established electrophysiological methods have limited clinical utility in the diagnosis of small fiber neuropathy. The cutaneous silent period (CSP) may be useful as a method for the evaluation of smaller and unmyelinated fiber dysfunctions. Hyperlipidemia is a very rare cause of small fiber neuropathy. In this study, hyperlipidemia and small fiber neuropathy in symptomatic patients with normal nerve conduction studies were evaluated with autonomic tests and cutaneous silent periods. Methods. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Glucose variation is a well-known factor for PNP but not the only one [75]. Hyperlipidemia can cause neuropathy similar to diabetic neuropathy regarding symptoms progression [76,77]. Plasma lipid levels are associated with many peripheral neuropathies, including axonal distal polyneuropathy, vision and hearing loss, motor nervous system lesions, and sympathetic nervous system dysfunction.…”
Section: Metabolic Comorbidities and Nerve Damagementioning
confidence: 99%
“…Glucose variation is a well-known factor for PNP but not the only one [75]. Hyperlipidemia can cause neuropathy similar to diabetic neuropathy regarding symptoms progression [76,77]. Plasma lipid levels are associated with many peripheral neuropathies, including axonal distal polyneuropathy, vision and hearing loss, motor nervous system lesions, and sympathetic nervous system dysfunction.…”
Section: Metabolic Comorbidities and Nerve Damagementioning
confidence: 99%
“…Besides central nervous system damage, diabetic patients exhibiting severe lipid metabolic disorders are at a higher risk of DPN than those without lipid disorders [ 6 ]. In addition, a study with cutaneous silent periods and autonomic tests demonstrated that mixed hyperlipidemia is associated with neuropathy in small fiber [ 7 ]. It is similar with another clinical research which indicated that individuals with normal weight had a significant lower prevalence of DPN (46.99%) than those (66.62%) with obesity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…, 2012, McArthur, 2012, Gibbons, 2014). The etiologies associated with SFN are numerous and include common metabolic disorders such as diabetes mellitus (Russell and Zilliox, 2014) and hyperlipidemia (Morkavuk and Leventoglu, 2013), infectious diseases such as HIV (Kaku and Simpson, 2014) and herpesviral infections (Steiner, 2012), as well as rare hereditary (Brouwer et al , 2014) and autoimmune conditions (Oomatia et al. , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestations of SFN typically involve a spectrum of positive and negative sensory abnormalities that may include neuropathic pain, paresthesias (spontaneous tingling or burning sensations), hyperalgesia, and numbness (Hoeijmakers et al 2012; McArthur 2012; Gibbons 2014). The etiologies associated with SFN are numerous and include common metabolic disorders such as diabetes mellitus (Russell and Zilliox 2014) and hyperlipidemia (Morkavuk and Leventoglu 2013), infectious diseases such as HIV (Kaku and Simpson 2014) and herpesviral infections (Steiner 2012), as well as rare hereditary (Brouwer et al 2014) and autoimmune conditions (Oomatia et al 2014). Relevant to neurotoxicology, several pharmaceutical compounds, including chemotherapeutic agents (Cavaletti et al 2010) and antiretroviral drugs (Cherry et al 2003; Ellis et al 2008; Dorsey et al 2015), have frequently been associated with peripheral neurotoxicity leading to SFN.…”
Section: Introductionmentioning
confidence: 99%